Cartography in Central and Eastern Europe Selected Papers of the 1st ICA Symposium on Cartography for Central and Eastern Europe - Gartner, Georg.; Gartner, Georg.; Ortag, Felix.; Ortag, Felix. (Lecture Notes in Geoinformation and Cartography, 2010)
The region of Central and Eastern Europe has a rich and long history in cart- raphy. Many important improvements in mapping and cartography have been proposed and performed by cartographers and researchers of that region. The long and outstanding history has led to a lively and vivid presence. Now contemporary methods for depicting the earth and its cultural and natural attributes are used. This book focuses on the contemporary activities in all major realms of cartography in Central and Eastern Europe. It covers aspects of theoretical, topographical, thematic and multimedia cartography, which have been presented at the frst Symposium on Cartography for Central and Eastern Europe, which took place from February 16th to 17th, 2009 in Vienna, Austria and was organized by the International Cartographic Association (ICA) and the Vienna University of Technology. The symposium’s aim was to bring together cartographers, GI scientists and those working in related disciplines from CEE with the goal of offering a platform for discussion and exchange and stimulation of joined projects. About 130 scientists from 19 countries followed the invitation and visited Vienna, Austria. A selection of fully reviewed contributions is edited in this book and is meant as a mirror of the wide range of activities in the realm of cartography in this region. The innovative and contemporary character of these topics has lead to a great variety of interdis- plinary contributions. Topics cover an enormous range with heterogenous relati- ships to the main book issues.